PRECISE MEASUREMENT OF CARBON DIOXIDE IN AQUEOUS SOLUTIONS USING A SIMPLE DISTILLATION METHOD - Al-Mutairi, Khalid Fahad (Global Journal of Chemistry, Biology and Physics (GJCBP), 2023)
High-pressure solvent extraction (HPSE) has gained significant popularity in the chemical, food, and pharmaceutical industries due to its efficiency and selectivity. Carbon dioxide (CO2) extraction, in particular, has emerged as a promising technique for obtaining flavors and fragrances from plant materials. Traditional extraction methods, such as steam distillation and solvent extraction, often necessitate additional processing steps and exhibit lower selectivity compared to CO2 extraction. HPSE, characterized by lower temperature and minimal water content, prevents thermal degradation and hydrolysis, resulting in extracts that retain the plant's active compounds and preserve the original scent. This research focuses on the application of HPSE to extract valuable compounds from marigold (Calendula officinalis L.), a widely cultivated plant with diverse applications in Europe and America. Traditional folk medicine employs marigold flowers for treating various ailments, including inflammatory conditions, gastrointestinal ulcers, and convulsions. Additionally, calendula extracts find use in dermatological preparations such as ointments for addressing conditions like ulcers, eczema, burns, and hemorrhoids. Pharmacological studies of conventional marigold extracts, including infusions, tinctures, and fluid extracts, have revealed the presence of important constituents, including saponins, glycosides of sesquiterpenes, flavonoids, and triterpenes. This study explores the potential of HPSE to extract and preserve these valuable compounds from marigold, thereby offering a novel and efficient approach for the pharmaceutical and cosmetic industries to harness the plant's medicinal and aromatic properties.